Analisis Mantan Narapidana Korupsi sebagai Calon Kepala Daerah dalam PKPU Nomor 9 Tahun 2020 dari Perspektif Etika Politik Islam - Ambodo, Triyo (Lembaga Penelitian Universitas Pangeran Diponegoro Nganjuk, 2025)
The General Election Commission Regulation (PKPU) Number 9 of 2020 governs the nomination of regional heads, including provisions for former corruption convicts. From the perspective of Islamic political ethics, it is crucial to analyze this policy to understand its implications for leadership integrity and public morality. Islamic political ethics emphasizes that leaders should possess noble character and be free from disgraceful acts, such as corruption. Therefore, although legally former corruption convicts may run for office after meeting certain requirements, from the standpoint of Islamic political ethics, this may be considered inconsistent with the principles of clean and trustworthy leadership. This analysis highlights the importance of considering moral and ethical values in the regional head election process to ensure the establishment of a government that is both integral and trusted by the public